2008
DOI: 10.1300/j077v26n01_03
|View full text |Cite
|
Sign up to set email alerts
|

The Phenomenology and Screening of Clinical Depression in Cancer Patients

Abstract: Clinical depression is the most common psychiatric disorder among cancer patients and is associated with significant functional impairment. Unfortunately, depression in cancer patients is often under- diagnosed and untreated, and studies examining the predictive utility of assessment instruments in detecting clinically depressed cancer patients are sparse. Using a structured interview, thirty-three patients with various cancer types were diagnosed as having major depression (n = 24) or no psychiatric diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
80
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 54 publications
3
80
0
2
Order By: Relevance
“…However, its criterion validity has been evaluated in only two, smallscale studies focusing exclusively on major depression [34,56]; in one of these, its specificity was inferior to that of the HADS-T (see Table 10 above). Future studies are needed to evaluate the validity of items assessing problems with sleep, appetite and concentration in samples on active treatment.…”
Section: Ces-dmentioning
confidence: 99%
“…However, its criterion validity has been evaluated in only two, smallscale studies focusing exclusively on major depression [34,56]; in one of these, its specificity was inferior to that of the HADS-T (see Table 10 above). Future studies are needed to evaluate the validity of items assessing problems with sleep, appetite and concentration in samples on active treatment.…”
Section: Ces-dmentioning
confidence: 99%
“…The scale is a valid and reliable measure of life satisfaction (Frisch, 1999) and is sensitive to change following cognitive-behavioral therapy for depression (Hopko et al, 2008b). The measure also has been shown to effectively discriminate depressed (M = -1.0, SD = 1.3) from nondepressed (M = 2.3, SD = 1.6) cancer patients (Hopko et al, 2008a).…”
Section: Assessment Measuresmentioning
confidence: 99%
“…The instrument has adequate psychometric properties in clinical and nonclinical samples of adults (Stanley, Beck, & Zebb, 1998;Zimet et al, 1988) and has been shown to effectively discriminate depressed (M = 36.0, SD = 18.6) from nondepressed (M = 24.2, SD = 19.4) cancer patients (Hopko et al, 2008a).…”
Section: Assessment Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Sin embargo, al compararla con otros instrumentos, como el HADS, obtiene menores propiedades psicométricas, por lo que su uso se recomienda sólo parcialmente. 26,27 Otro instrumento utilizado es la escala de depresión posnatal de Edimburgo (EPDS) que está formada por 10 reactivos, los cuales se enfocan primordialmente a síntomas no físicos relacionados con la depresión post parto, por tal razón, se ha aplicado a población con cáncer terminal y ha mostrado en tres estudios una especificidad, sensibilidad, confiabilidad inclusive mayor que las reportadas en algunos trabajos que utilizan el HADS. No obstante los buenos resultados, son necesarios más estudios para recomendar ampliamente su uso.…”
Section: Pacientes Paliativosunclassified